Inefficiencies and market power in financial arbitrage: a study of California's electricity markets - Christopher R. Knittel; Catherine Wolfram; James Bushnell; Severin Borenstein (University of California, Department of Economics, 2006)
As with other commodities, electricity is often traded on both forward and spot markets. This was initially true in the restructured California electricity ndustry from 1998 to 2000. Though the power traded in the forward and spot markets was for delivery at the same times and locations, prices often differed in significant and predictable ways. We consider several explanations for this apparent inefficiency, concluding that uncertainty about regulatory penalties for trading in the spot market caused most firms to avoid trading on inter-market price differences. The few firms that did carry out these trades did not find it profit-maximizing to eliminate the price differences. Skyrocketing prices in the summer of 2000, however, changed the major buyers' (utilities') incentives and increased the price differentials between the markets.
Keywords: 330